Palestinian ethnonationalism in Israel - Haklai, Oded, 1972- (National and ethnic conflict in the 21st century., 2011)
This carefully researched and insightful investigation of the rise of a new Arab movement within Israel has important implications for the Palestinian-Israeli conflict as a whole.